Mobile Phone-Based CIPP Evaluation Model in Evaluating the Use of Blended Learning at School in Bali - Divayana, Dewa Gede Hendra; Sanjaya, Dewa Bagus (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Through the use of information technology, the students no longer find it difficult to look for sources/learning materials, interact and discuss with each other any time and any where they are.  One form of the roles of information technology which can facilitate students in individual learning, group learning and learning together with the teacher in the classroom and outside of the classroom is blended learning. The fact in schools shows that not all of the learning process can be optimized by using blended learning. Therefore, there is a need to evaluate comprehensively any time and any where they are (evaluators). For this purpose, the appropriate evaluation model to be used is mobile phone-based CIPP. By using this model, then the evaluator can study evaluating the use of blended learning overall through of the context, input, process and product that will be able to provide appropriate recommendations for the improvement of the learning process using blended learning in school.